The consequences of non-participation in the Paris Agreement - Mario Larch; Joschka Wanner (European Economic Review, 2024)
International cooperation is at the core of multilateral climate policy. How is its effectiveness harmed by individual countries not participating in the global mitigation effort? We use a multi-sector structural trade model with carbon emissions from production and a constant elasticity of fossil fuel supply function to simulate the consequences of unilateral non-participation in the Paris Agreement. Taking into account both direct and leakage effects, we find that non-participation of the US would eliminate more than a third of the world emissions reduction (31.8% direct effect and 6.4% leakage effect), while a potential non-participation of China lowers the world emission reduction by 24.1% (11.9% direct effect and 12.2% leakage effect). The substantial leakage is primarily driven by technique effects induced by falling international fossil fuel prices. In terms of welfare, the overwhelming majority of countries gain from the implementation of the Paris Agreement and most countries have only very little to gain from unilaterally deciding not to participate.
Keywords: F14; F18; Q56; 330; Climate change; International trade; Carbon leakage; Fossil fuel supply